Aspects of Baghdadi Society in Contemporary Iraqi Painting: Comparative Methods (Journal of the College of Basic Education, 2022)
The development of art, intellectually and aesthetically, necessitates the imposition of fundamental principles that affect the city as a society and the human being as an individual, despite the complexities of social development. Such as the freedom of the creative human self and the freedom of experimentation and discovery in thought and art. The civilized city prepares the prerequisites for social integration, so that scientific, intellectual and cultural development is the basis of its daily existence, and it is a nurturing environment for human activities, including the arts. And since drawing is a civilized characteristic of the civil society, it arises and develops in the civilized city and is required by the integration of society in it.